1941
DOI: 10.1021/ie50376a020
|View full text |Cite
|
Sign up to set email alerts
|

Mildew-Resistant Treatments on Fabrics

Abstract: Table VIII. Comparison of Sapwood and Heartwood Wood species Chip0 source White Birch Spruce Sap-Heart-wood& wood& wood6 wood6 wood6 wood6 Yield, % 44.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1942
1942
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Since it is difficult to determine what is being furnished and agars from different sources vary in their usable constituents, it would seem advisable to eliminate this variable. 4. It has been found essential to change the sodium nitrate to some other nitrogen source, because the utilization of the nitrate radical by most fungi resulted in a medium too alkaline for their development.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is difficult to determine what is being furnished and agars from different sources vary in their usable constituents, it would seem advisable to eliminate this variable. 4. It has been found essential to change the sodium nitrate to some other nitrogen source, because the utilization of the nitrate radical by most fungi resulted in a medium too alkaline for their development.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of copper naphthenate in pureculture, soil-burial, and soil-suspension fabric tests has been reported by various authors [2,16,17,34,50,51,86,87,131,132] . Although &dquo;naphthenic acid&dquo; is a complex mixture of substances which undoubtedly varies in composition from one source to another, it has been common experience among workers in the field of fabric mildew preventives to find that copper naphthenates from various sources possess unusual fungicidal properties not common to most other copper compounds.…”
Section: Use Of Mildew Preventivesmentioning
confidence: 94%
“…Copper pentachlorophenate, the copper salt of 8-hydroxyquinoline, zinc dimethyl dithiocarbamate, mercaptobenzothiazole, phenyl mercury acetate-these and many others have been investigated in laboratory studies but have apparently not been extensively used in practice. A cadmium soap treatment effective against Chaet01niul11 globosum was described by Furry et al [50] . Fargher, Galloway, and Probert [43] mention the high fungicidal activity of thallium carbonate, o-chloromercuriphenol, ~-acetoxymercuriacetanilide, p-nitrophenol, and trichlorophenol but conclude that none of these is practical for incorporation into sizing to prevent mold growth.…”
Section: Use Of Mildew Preventivesmentioning
confidence: 99%
“…Tannins possess in their molecules several o-dihydroxyphenyl groups which are excellent chelators of metal ions. In appropriate conditions they precipitate copper(II) ions quantitatively (McDonald et al 1996) and previous papers have shown that plant polyphenols such as catechu (Fury et al 1941), loblolly pine bark extracts rich in condensed tannins (Laks et al 1988;Lotz and Hollo way 1988) or lignin (Ohlsson and Simonson 1992) can be used to fix copper(II) within wood. One of the main quality of these treatments is their relative innocuousness for humans and the environment.…”
Section: Introductionmentioning
confidence: 99%